2004
DOI: 10.1002/bjs.4805
|View full text |Cite
|
Sign up to set email alerts
|

Radioisotope bone scans in the preoperative staging of hepatopancreatobiliary cancer

Abstract: Bone scanning should not be included in the routine staging protocol for HPB cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Despite the revised amendments, it is limited only to HCC patients with early stage for LT candidate. Given the high false positive rates of bone scans and the low incidence of extrahepatic metastases in patients with early staged HCC [8,9,12], unnecessary or futile radiologic examinations during staging workup in all HCC patients at each tumor stage should be avoided. To date, however, there have been no evidence-based recommendations on the use of chest CT and bone scans during initial staging workup of HCC patients at each tumor stage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the revised amendments, it is limited only to HCC patients with early stage for LT candidate. Given the high false positive rates of bone scans and the low incidence of extrahepatic metastases in patients with early staged HCC [8,9,12], unnecessary or futile radiologic examinations during staging workup in all HCC patients at each tumor stage should be avoided. To date, however, there have been no evidence-based recommendations on the use of chest CT and bone scans during initial staging workup of HCC patients at each tumor stage.…”
Section: Introductionmentioning
confidence: 99%
“…Although a few studies have evaluated the usefulness of chest CT and bone scans in HCC patients [8][9][10], most were limited due to the small number of subjects and the inclusion of patients with cholangiocarcinoma. The United Network for Organ Sharing (UNOS) policy item 3.6.4.4 (1998) recommended that chest CT and bone scans to detect metastases should be performed on HCC patients who are candidates for liver transplantation (LT) [11], but this recommendation was based on clinical consensus rather than accumulated evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the recommendation to screen for metastasis in patients with early-stage HCC as a requirement for inclusion on the LT waiting list is not evidence-based. Recently, some research groups investigated the frequency of bone metastases (BM) and the utility of bone scans (BSs) in the pre-LT assessment of this patient population [13,14]. These studies showed that, in view of the low frequency of metastases, BSs should only be performed in this setting in patients with clinical signs or symptoms indicative of bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Bone is the other preferred site of spread, and although UNOS had included bones scans in the policies implemented in the 1990s, in light recent evidence provided by several studies, this decision was amended in their most recent liver allocation statements. The significant number of false positive or indeterminate results obtained with this modality is a major disadvantage, as well as the costs incurred for a study that has little impact in the selection of patients given its negligible true-positive yield (Koneru, 2005;Sheth, 2005).…”
Section: Other Imaging Studiesmentioning
confidence: 99%